2009
DOI: 10.5194/angeo-27-1097-2009
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatic transfer functions revisited: Little Ice Age and Medieval Warm Period summer temperatures reconstructed using artificial neural networks and linear algorithms

Abstract: Abstract. Tree-rings tell of past climates. To do so, tree-ring chronologies comprising numerous climate-sensitive livingtree and subfossil time-series need to be "transferred" into palaeoclimate estimates using transfer functions. The purpose of this study is to compare different types of transfer functions, especially linear and nonlinear algorithms. Accordingly, multiple linear regression (MLR), linear scaling (LSC) and artificial neural networks (ANN, nonlinear algorithm) were compared. Transfer functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 89 publications
(137 reference statements)
2
41
0
Order By: Relevance
“…The wamth around the turn of the first millennium AD was seen closely synchronous with the MXD and TRW evidence from northern Fennoscandia (Grudd, 2008;Esper et al, 2012) and northern Finland (Helama et al, 2009a(Helama et al, , 2009b(Helama et al, , 2010a(Helama et al, , 2010b(Helama et al, , 2012b. The northern MXD (Esper et al, 2012) and TRW (Helama et al, 2010a) reconstructions showed their warmest 250-year periods in AD 816-1065 and AD 932-1181, respectively.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The wamth around the turn of the first millennium AD was seen closely synchronous with the MXD and TRW evidence from northern Fennoscandia (Grudd, 2008;Esper et al, 2012) and northern Finland (Helama et al, 2009a(Helama et al, , 2009b(Helama et al, , 2010a(Helama et al, , 2010b(Helama et al, , 2012b. The northern MXD (Esper et al, 2012) and TRW (Helama et al, 2010a) reconstructions showed their warmest 250-year periods in AD 816-1065 and AD 932-1181, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Long instrumental summer temperature records were also available in adjacent areas from St. Petersburg (Jones and Lister, 2002) 1801-1804, 1992-1994 and 2001. Summer temperature reconstructions from northern Finland and northern Fennoscandia were available over the study period, based on tree-ring width (Helama et al, 2009a(Helama et al, , 2009b(Helama et al, , 2010a and MXD data (Esper et al, 2012), respectively. These records were filtered using a spline function (Cook and Peters, 1981) with the rigidity of 50-years (50% frequency cut-off) and compared with the new palaeoclimate evidence by visual inspection and Pearson correlations (r).…”
Section: Proxy Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations